Cytotoxic effects of Phyllanthus watsonii Airy shaw extract in combination with cisplatin on human ovarian cancer cell / Farhana Raduan - Farhana , Raduan (2018)
Ovarian cancer is the major gynaecological cancer that causes female mortality worldwide and its treatment involved chemotherapy drug of platinum based-drugs. The disadvantages of these treatments are patients experience severe side effects and drug resistance. Drug combination therapy is the gold standard treatment for cancer management with objectives to encounter resistance and decreasing or increasing doses safely without sacrificing efficacy. One such combination is between chemotherapy drug and plant extract. Phyllanthus watsonii Airy Shaw, an endemic plant of Peninsular Malaysia exhibited good anticancer effect on various human cancer cell lines. This study is aimed to investigate the cytotoxicity and possible interaction (additive, synergistic or antagonist) of P. watsonii and cisplatin (Pt) combination on human ovarian SKOV-3 cancer cell. P. watsonii ethyl acetate extract (PW-E) was extracted from the leafy part using a series of solvent extraction and the chemical profile was analysed by LC-MS/MS system. Cytotoxicity of PW-E, Pt and PW-E/Pt combination on SKOV-3 cells were determined using the Neutral Red Uptake assay and the inhibitory concentrations (IC50) of single and combined dosage, Combination Index (CI) and other parameters were analysed using CompuSyn 1.0 software. Cell death mechanism triggered by the single and combination dosage on SKOV-3 cells was determined by morphological imaging under phase-contrast microscope, AO/EB double staining and caspase-3 activation assay. LC-MS/MS analysis of PW-E revealed the presence of gallic acid, strictinin, strictinin isomer, galloyl HHDP hexoside, hyperin, ellagic acid, kaempferol glucoside, kaempferol rhamnoside and quercetin. Cytotoxic effects of PW-E, Pt and PW-E/Pt combination were observed in dose-dependent manner after 72 hours incubation with IC50, 1.78 ± 0.32 μg/ml, 0.69 ± 0.11 μg/ml and 1.34 ± 0.16 μg/ml (P<0.05) respectively. The combination was considered highly selective towards cancer cell as compared to normal lung fibroblast MRC-5 cells based on the selectivity index (SI>3). CI analysis revealed two important data; (i) synergistic effect (CI<1) was observed at IC50, while at higher doses of the combination exert antagonist effect (CI>1); and (ii) Drug Reduction Index (DRI) revealed a reduction of the extract to about 1.64-fold (1.07 μg/ml) and drug, 2.56-fold (0.27 μg/ml) in combination to achieve similar 50% inhibition as individual treatment, indicating reduction of dosage of both the extract and drug while maintaining efficacy. Morphological examination under phase-contrast of SKOV-3 cells showed typical apoptotic changes i.e, membrane blebbing, cell shrinkage and apoptotic bodies and were enhanced in cells underwent PW-E/Pt combination treatment. Staining with AO/EB revealed condensed and fragmented chromatin more clearly. Caspase-3 activation was increased in Pt, PW-E and PW-E/Pt combination with increment of 38%, 13% and 31% respectively which indicated that caspase-3 may involve in SKOV-3 cell apoptosis. However, the data is not significant (p>0.05). In conclusion, the present study revealed, PW-E/Pt combination exert cytotoxic effect on SKOV-3 cells via doses reduction and with possible synergistic interaction and mediated by apoptotic pathway.